Pembelajaran Tanggap Budaya (Culturally Responsive Teaching) di Kelas IV Sekolah Dasar - Sisriawan Lapasere; Nengsih Julianti; Herlina Herlina; Rizal Rizal; Ammar Abdullah Joni Guci (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to identify how to implement culturally responsive teaching in grade IV of SDN Inpres 1 Birobuli. The method used was qualitative descriptive with the subject of grade IV students of SDN Inpres 1 Birobuli, the respondents of this study were students with a total of 27 people and teachers of grade IV A of SDN Inpres 1 Birobuli. The instruments in this study are observation sheets, interview guidelines, document studies and questionnaires. Data collection was carried out by conducting observations, interviews, document studies, and questionnaires. The data analysis used was a qualitative analysis from Miles and Huberman. The results of the research show that the implementation of culturally responsive teaching at SDN Inpres 1 Birobuli has created inclusive and meaningful learning by integrating local culture. This method improves students' understanding, motivation, and tolerance, although it still needs optimization in all subjects. If this method is applied more consistently, it is expected to produce a younger generation that appreciates cultural diversity. The implication of this study is that the implementation of culturally responsive teaching (CRT) at SDN Inpres 1 Birobuli can create inclusive and meaningful learning by integrating local culture, which enhances students' understanding, motivation, and tolerance towards diversity. Although it has shown positive results, the implementation of this method still needs to be optimized across all subjects. Therefore, continuous efforts are required in teacher training and providing teaching materials that support the integration of local culture in learning, in order to produce a younger generation that appreciates and preserves Indonesia's cultural diversity.